Performance of sulfur-based autotrophic denitrification process for nitrate removal from permeate of an MBR treating textile wastewater and concentrate of a real scale reverse osmosis process - Yılmaz, Tülay; Sahinkaya, Erkan (Elsevier BV, 2023)
Textile is one of the industrial sectors generating the highest amount of wastewater with various polluting substances. Lately, water reuse in textile industries, especially, with the reverse osmosis (RO) process following membrane bioreactor (MBR) treatment has been applied more commonly. In this study, an autotrophic sulfur-based denitrifying column performance was evaluated, for the first time, for nitrate reduction from permeate of a lab-scale MBR receiving real textile wastewater and from the concentrate stream of a real scale-RO plant used for recovering water from textile wastewater. Nitrate concentration in the MBR effluent and RO concentrate averaged 35 ± 3 and 12 ± 2 mg-N/L, respectively. With the sulfur-based column bioreactor, quite high (≥90%) denitrification performances were attained both for MBR effluent and RO concentrate up to nitrate loadings of 0.432 and 0.12 g-N/(L.d), respectively. COD present in wastewater was not utilized in the column bioreactor, which illustrates no or minimal contribution of heterotrophic denitrification. Alkalinity concentration in the wastewater was enough to buffer the acid formation during autotrophic denitrification. Sulfate was generated accompanied by nitrate reduction and sulfide was formed at low nitrate loadings. In the batch tests, the denitrification rates for the MBR effluent and RO concentrate were 0.31 and 0.28 g-N/(g-VSS.d), respectively, which were relatively higher than the ones observed for the synthetic nitrate-contaminated groundwater. Autotrophic sulfur-based denitrification is a promising and robust process alternative even for textile RO concentrate with high concentrations of salinity, non-biodegradable COD, and color.
Keywords: Autotrophic Processes; Osmosis; Nitrates; Bioreactors; Textiles; Denitrification; Wastewater; Sulfur